Cosmeceutical Potentials of Equisetum debile Roxb. ex Vaucher Extracts - Phanit Thammarat; Jutamas Jiaranaikulwanitch; Rungsinee Phongpradist; Araya Raiwa; Hataichanok Pandith; Kasirawat Sawangrat; Sasithorn Sirilun (Applied Sciences, 2023)
Trends in skin and hair treatments focus on natural products due to undesired effects of chemically synthetic ingredients. This study aims to investigate the cosmeceutical effects of Equisetum debile (horsetail) extracts relating to anti-hyperpigmentation via tyrosinase, anti-wrinkle formation via matrix metalloproteinases (MMPs), and anti-androgenic alopecia via 5α-reductase. Ethanolic extracts were sequentially partitioned into semi-purified fractions hexane, dichloromethane, ethyl acetate, methanol, and methanol insoluble residue. The ethyl acetate fraction possessed the highest total phenolic content (39.24 ± 0.72 mg gallic acid/g), the strongest anti-tyrosinase activities (583.33 ± 23.59 mg kojic acid/g), and potent collagenase inhibitions (IC50 MMP-1 and MMP-2 of 0.82 ± 0.09 and 0.94 ± 0.11 mg/mL, respectively). All extracts showed considerable inhibitions of 5α-reductase ranging from 44.59 ± 0.40 to 83.07 ± 3.46% with the strongest activity from the dichloromethane fraction (1.48 ± 0.06 mg finasteride/g). In conclusion, E. debile extracts exhibit cosmeceutical potentials. This study suggests that the E. debile ethyl acetate fraction could be used as a promising ingredient to organically treat hyperpigmentation and delay the skin aging process. In addition, compared to the current recommended intake of finasteride (1 mg/day) for androgenic alopecia, the dichloromethane fraction is proposed as an alternative source to naturally remediate hair loss.